Progress in the Face of Insecurity : Improving Health Outcomes in Afghanistan - World Bank Group (World Bank, Washington, DC, 2018)
Afghanistan has made strong gains in health outcomes, health service coverage andhealth systems performance since 2003, with a particular impact on women and children's health. All told, Afghanistan has made notable progress towards achieving the Millennium Development Goal (MDG) targets for improving maternal (MDG5) and child health (MDG4). According to United Nations estimates, maternal mortality rates (MMR) declined from 1,100 to 396 deaths per 100,000 live births from 2000 to 2015 (Alkema and others 2016), and under-5 child mortality rates (U5MR) fell 34 percent (from 137 to 91 deaths per 1,000 live births). Newborn mortality rates (NMR) dropped 32 percent (from 53 to 36 deaths per 1,000 live births) (You and others 2016). Nevertheless, it is important to emphasize that in absolute terms there is considerable room for progress.